Correlation of Levels of Levels (PB) in Blood With Blood Profile of Metal Forging Workers - Indah Tri Susilowati; Tri Harningsih; Dinar Agrita; Agung Cahyany Prasetyo; Yosefina Prameska Winanto Saputri; Siti Fatimah (GLOBAL HEALTH SCIENCE GROUP, 2022)
Metal smelting has the potential to release micro-sized metal particles into the air. One of the metal smelting household industries is the gamelan industry. Brass is the basic material for making gamelan with a lead (Pb) content of 0.46%. In the process of making this gamelan, gamelan craftsmen will have a risk of exposure to Pb particles. Absorbed lead will be transported in the organs of the body as much as 95%, in the blood lead will be bound by erythrocytes and will interfere with the formation of hemoglobin. This study aims to see the relationship between Pb levels and the blood profile of metal forging workers in the gamelan industry, Wirun Mojolaban Village, Sukoharjo. This research is a quantitative, observational study with a sample size of 35 gamelan craftsmen in Wirun Village, Mojolaban Sukoharjo. The examination of Pb levels was carried out at BLK Jogja with GFAAS, while the examination of hemoglobin, leukocytes, platelets, hematocrit, and erythrocytes was carried out in the clinical laboratory. The results showed that there was no relationship between Pb levels in the blood and the number of hemoglobin, leukocytes, platelets, hematocrit, and erythrocytes. Although gamelan craftsmen are exposed to lead, they have not shown any symptoms of poisoning and have no blood disorders.